Evaluation of Antipyretic and Antioxidant Activities of Ten Indigenous Medicinal Plants of Tirtajaya, Karawang Regency, West Java, Indonesia - Gunarti, Neni Sri; Alkandahri, Maulana Yusuf; Wahyuningsih, Eko Sri; Agustina, Putri; Mursal, Iin Lidia Putama; Hidayah, Himyatul; Nurviana, Vera (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim This research aimed to explore the antipyretic and antioxidant activity of infusions of Chromolaena odorata (COI), Abelmoschus manihot (AMI), Annona muricata (AMCI), Allium ascalonicum (AAI), Carica papaya (CPI), Tamarindus indica (TII), Zingiber officinale (ZOI ), Abrus precatorius (API), Momordica charantia (MCI) and Strobilanthes crispus (SCI). Materials and Methods The antipyretic activity of plant infusions was tested using a peptone-induced rat model. The male rat used were divided into 32 groups for each test. Each group consisted of four rats, including a negative control, a positive control (paracetamol 150 mg/kg) and groups COI, AMI, AMCI, AAI, CPI, TII, ZOI, API, MCI and SCI, each administered doses of 100, 200 and 400 mg/kg. Initial rectal temperature was recorded using a rectal thermometer at a depth of 1.5 cm in the rat rectum. Fever induction was confirmed by a temperature rise of more than 0.5°C. After drug administration, rectal temperature was recorded periodically at 1, 2, 3 and 4 hr. Furthermore, antioxidant activity was tested using the DPPH method. Results The results showed that administration of COI, AMI, AMCI, AAI, CPI, TII, ZOI, API, MCI and SCI was able to significantly reduce the rectal temperature of febrile rat which depended on dose and time. The antioxidant test results indicated that AAI exhibited very strong antioxidant intensity, while AMCI, CPI, ZOI, API and SCI showed strong antioxidant intensity, COI and MCI had medium antioxidant intensity, AMI had weak antioxidant intensity and TII displayed very weak antioxidant intensity. Conclusion Based on the results, it can be concluded that COI, AMI, AMCI, AAI, CPI, TII, ZOI, API, MCI and SCI exhibit antipyretic and antioxidant activity.
Keywords: Antipyretic; Antioxidant; Medicinal plants; Peptone-induced rat model; DPPH